Antioxidant Testing of Manggo Constraint Leaves Extract (Dendrophthoe Pentandra) Dekokta Results - Umarudin; Octifany, Salsabila; Kusumo, Galuh Gondo; Aristyawan, Andhika Dwi; Yuliarni, Floreta Fiska; Renaisansa, Ramadhan; Pertiwi, Husadhani Dwi (Universitas Muhammadiyah Lamongan, 2025)
Mango mistletoe leaves have been identified as a natural source of antioxidants because they contain the quarcetin. The aim of this research is to determine whether mango mistletoe Dendrophthoe pentandra leaf extract extracted using the dekokta method has antioxidant activity if tested using the DPPH method. This research was carried out by extracting samples of mango mistletoe leaf powder Dendrophthoe pentandra using the decoction method, the extract obtained was tested for antioxidant activity using the DPPH method using UV-Vis spectrophotometry with a comparison in the form of vitamin C. The results of the mango mistletoe leaf extract was tested at a wavelength of λ 521.5 nm obtained with an IC50 value of 322.80 ppm, with SD ± 107.08 and RSD 33.17%. while for ascorbic acid the IC50 value was 53.89 ppm, with SD ± 6.39 and RSD 11.86%. This research can be concluded that the dekokta mango mistletoe leaf extract has very weak antioxidant activity while ascorbic acidhas relatively strong antioxidant activity. It would be advisable to measure the levels of secondary metabolites contained in the extract of mango mistletoe and it is necessary to carry out research on the antioxidant activity of mistletoe mango leaf extract using methods other than the DPPH method. Keywords - Antioxidants; Decoction; Dendrophthoe pentandr; DPPH.